EFEKTIFITAS SUPPORTIVE EDUCATIVE NURSING INTERVENTION (SENI) DALAM MENURUNKAN INTERDIALYTIC WEIGHT GAIN (IDWG) PADA PASIEN HEMODIALISA - Bardah Wasalamah; Feni Eka Dianty; Esti Sorena (Jurnal Kesehatan Medika Saintika, 2023)
Fluid restriction is the hardest regimen to follow in chronic kidney disease patients receiving hemodialysis, leading to an increase of Interdialytic Weight Gain (IDWG) with several complications. Supportive Educative Nursing Intervention (SENI) Orem's theory is innovative method with the goal of enhancing fluid restriction and thus have a positive impact on controlling IDWG as an objective marker of fluid restriction adherence. This study aimed to determine the effect of Supportive Educative Nursing Intervention (SENI) on Interdialytic Weight Gain (IDWG) of CKD patients receiving hemodialysis. This study adopted a quasi-experimental, pre and post test with control group. This study was conducted at the RSUD. Dr. M Yunus Bengkulu, Indonesia involving 80 hemodialysis patients. IDWG was measured by weight measurement before and after HD. Outcomes were measured before intervention, 1 week after intervention, and 2 weeks after intervention. Data analysis were carried out using Repeated ANOVA, and Independent sample t-test.  Repeated ANOVA test showed a statistically significant difference IDWG after 2 weeks of intervention between both of groups with greater decline in intervention group compared to the control group (p=0.013). Supportive Educative Nursing Intervention (SENI) Orem's theory  increases fluid restriction control as indicated by IDWG.Keywords: Chronic Kidney Disease (CKD), Hemodialysis, Supportive Educative Nursing Intervention (SENI), Interdialytic Weight Gain (IDWG)